Research progress on heteroterpene and meroterpenoid compounds from the Rhododendron genus and their NMR characterization and biological activity - Mao, Jingxin; Yang, Meiyan; Li, Tingting; Sun, Yan; Dong, Zhaoyue; Zhan, Honghong; Chen, Min (Frontiers in Pharmacology, 2025)
The plant genus, Rhododendron constitutes an important part of the treasure trove of traditional Chinese medicine and have made outstanding contributions to human health for centuries. There are approximately 25 species of Rhododendron plants in China that have been used in folk medicine. Among these, Dali, which is known as little Rhododendron, is one of the most commonly utilized species. Modern chemical and pharmacological studies have shown that the genus contains diverse chemical constituents, including terpenes, diterpenes, triterpenes, sesquiterpenes, monoterpenes of the resveratrol type, heteroterpenes, meroterpenoids, flavonoids, lignin, phenolic acids. Meroterpenoids are derived from terpenoid biogenic pathways, with a biosynthesis involving shikimic acid terpenoid adducts. Heteroterpenes, a class of terpenoids with diverse properties, are mainly derived from plants of the Rhododendron genus. This review manuscript collates 113 different terpenoid monomers identified in Rhododendron plants. Extracts of Rhododendron genus plants and purified terpenoid monomers exhibit numerous pharmacological effects, with anti-inflammatory, anticancer, analgesic, antibacterial, antioxidant, expectorant, anti-asthmatic, cough suppressant, and smooth muscle relaxation properties. The meroterpenoids and heteroterpenes have been shown to exhibit significant therapeutic effects in conditions such as ischemia-reperfusion injury and ischemic heart disease. The purpose of this article is to provide an overview of the chemical and pharmacological research on Rhododendron plants over the past 20 years, which may be of value in the development of new drugs or food supplements.